Thermal storage examination with Galerkin approach involving mixture of water and nanoparticles. (January 2023) - Mechai, Idir; Abu-Hamdeh, Nidal H.; Talabany, Ziyad Jamil; Ajour, Mohammed N.; Hatamleh, Randa I.; Musa, Awad
Abstract: With involving homogeneous model for incorporating nanomaterial impact on discharging of PCM, the mathematical models with unsteady terms were derived for this study. In this model, influences of shape of nano-powders were included in properties of nanomaterial. Discharging of water with the container with tilted fin attached to upper circular wall has been simulated and since there is low magnitude of liquid PCM, the associated term was discard and only two equations have been remained. For find more accuracy in solution, FEM with involving variable configuration of grid have been utilized and for validation purpose, published article with same numerical method was selected. The more magnitude of shape factor, the quicker solidification has been obtained. Increase of this factor makes the time of process to decrease around 5.83 % which is about 75.34 % greater impact in comparison to case with ϕ = 0.02. Inclusion of blade shape particle with highest fraction leads to reduction of period of freezing around 23.51 % and this effect for cylinder shape can be 25.23 % lower than the mentioned effect. Highlights: Impact of radial fins and nanomaterial on discharging was studied. Galerkin for modeling of solidification was hired. Using higher shape factor will reduce time about 5.83 %. Higher fraction of blade nanoparticle leads to reduce of time around 23.51 %.